RELATIONSHIP OF CAPITAL ADEQUECY RATIO (CAR), FINANCING TO DEPOSIT RATIO (FDR), NON PERFORMING FINANCING (NPF), AND RETURN ON ASSET (ROA) USING VECTOR AUTOREGRESSION (VAR) METHOD - Riyan Pradesyah; AL Bara (Proceeding International Seminar of Islamic Studies, 2022)
This study aims to see the relationship and influence between the variables Capital Adequecy Ratio (CAR), Financing to Deposit Ratio (FDR), Non Performing Financing (NPF), and Return On Asset (ROA), using the Vector Autoregression (VAR) method. The data used in this study is data on the financial statements of Islamic banks in Indonesia, starting from January 2016 to December 2021. As for the results obtained by the Granger Causality test, it was obtained that there is a reciprocal relationship between CAR, FDR, NPF and ROA, this is seen from the results of the Granger Causality Test, where the F-statistical value and Probability are not equal to 0. While simultaneously CAR, FDR, NPF affected ROA by 22.47%, this was seen from the results of the Variance Decomposition test. Keywords: CAR, FDR, NPF, ROA